Program Diskon Pada Minimarket Dalam Menarik Minat Pembeli - Pangestu, Chairunnisah; Andru, Budi; Utami, Novelia (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Nowadays, very tight business competition makes companies change strategies to achieve the goals they want to achieve, one of the strategies used is to provide discounts. The aim of the research is to determine the extent of the effectiveness of discounts in sales results at As-Salam Mart Bintara Jaya West Bekasi. The research method used is descriptive qualitative by conducting observations, interviews and documentation. The informants in this research are shop owners, shop employees, shop consumers. The focus of this research is discounts with discount indicators, a certain period of time, a certain amount. Providing discounts is expected to have an effect on the sales results of the products offered. The research results show that giving discounts at As-Salam Mart Bintara Jaya West Bekasi does not have a significant effect on sales results and consumer interest. The reasons found were many empty products, an uncomfortable atmosphere, and unattractive discounted products at that place.